Flexible and Multifunctional Silk Textiles with Biomimetic Leaf‐Like MXene/Silver Nanowire Nanostructures for Electromagnetic Interference Shielding, Humidity Monitoring, and Self‐Derived Hydrophobicity - Liu, Liu‐Xin; Chen, Wei; Zhang, Hao‐Bin; Wang, Qi‐Wei; Guan, Fanglan; Yu, Zhong‐Zhen (Advanced functional materials, 2019)
Although flexible and multifunctional textiles are promising for wearable electronics and portable device applications, the main issue is to endow textiles with multifunctionalities while maintaining their innate flexible and porous features. Herein, a vacuum‐assisted layer‐by‐layer assembly technique is demonstrated to conformally deposit electrically conductive substances on textiles for developing multifunctional and flexible textiles with superb electromagnetic interference (EMI) shielding performances, superhydrophobicity, and highly sensitive humidity response. The formed leaf‐like nanostructure is composed of silver nanowires (AgNWs) as the highly conductive skeleton (vein) and transition metal carbide/carbonitride (MXene) nanosheets as the lamina. The presence of MXene protects AgNWs from oxidation and enhances the combination of AgNWs with the fabric substrate, and the transformation of its functional groups leads to self‐derived hydrophobicity. The flexible and multifunctional textile exhibits a low sheet resistance of 0.8 Ω sq−1, outstanding EMI shielding efficiency of 54 dB in the X‐band at a small thickness of 120 µm, and highly sensitive humidity responses, while retaining its satisfactory porosity and permeability. The self‐derived hydrophobicity with a large contact angle of >140° is achieved by aging the hydrophilic MXene coated silk. The wearable multifunctional textiles are highly promising for applications in intelligent garments, humidity sensors, actuators, and EMI shielding. A biomimetic leaf‐like nanostructure composed of a 1D AgNWs skeleton (vein) and 2D MXene as the lamina is fabricated via vacuum‐assisted layer‐by‐layer assembly for electromagnetic interference (EMI) shielding, humidity monitoring, and self‐derived hydrophobicity. The (MA1)10 silk presents an exceptional EMI shielding effectiveness of ≈90 dB at 12.4 GHz at a thickness of 480 µm, and the MXene‐coated textile induces a hydrophilic‐to‐hydrophobic transition, generating a large contact angle of >140°.